Diagnóstico y propuesta de mejora para la cadena de abastecimiento de la línea de fluidos de perforación de una Compañía de Servicios Petroleros (2022)
This work presents a performance diagnosis for the drilling fluids service supply chain of an oilfield service company. In the first part the current situation of the supply chain is described and evaluated using tools as the business canvas model, the SWOT analysis and the autodiagnosis proposed by Rodolfo Torres Rabello in his work “Autodiagnóstico de cadenas de suministro”. Using the SCOR model the supply chain key process were defined, as well as the activities carried out in each process and the current problems by process.